Intelektualiści zachodnioeuropejscy od wybuchu II wojny światowej do współczesności - Tomczak, Maria (Studia Europaea Gnesnensia, 2015)
This study aims to show the forms of political involvement of Western European intellectuals. In doing so, the paper attempts to answer the question about the role they played in Western and Central Europe in the discussed period. The paper also demonstrates the cultural and political causes of their decline. streszczenie For the intellectuals of Western and Central Europe, World War 2 was an extremely difficult period. The genocidal policies of the totalitarian states induced them to take a position, while at the same time depriving them of the ability to express their views publicly. This engendered a sense of helplessness; also, apart for a few exceptions, only emigrants could actually perform the function of intellectuals. Among those, an important role to play fell to two groups: German emigrants who distanced themselves from their nation, and Jewish emigrants, who addressed the subject of the Holocaust. After the war, the Iron Curtain also restricted the actions of intellectuals. It soon turned out that the tenor of spiritual life was set by left-wing authors, fascinated with the USSR. The fascination petered out after the disclosure of Stalin’s crimes in 1956. It was terminated definitively by the ruthless suppression of the Prague Spring. It was at that time that conservatism and right-wing intellectuals returned to Europe. Their aim was to reverse the trend and prevent Western Europe from drifting leftward. The change of the paradigm served to settle the scores with the leftist intellectuals. They were accused of subversive activities against the state and nation or treason. Also, in the intellectual circles there emerged a conviction that the previous formula had been exhausted. A new formula of activities of intellectuals was considered particularly in France, by authors of such eminence as R. Aron, M. Foucault, or P. Bourdieu. The deconstruction of the figure of the intellectual was completed by J.-F. Lyotard, who pronounced the death of intellectuals. Involvement of intellectuals remained a valid notion only in the countries of the Eastern bloc. In post-Cold War Europe, the decline of intellectuals became even more discernible. This was occasioned by a number of political and cultural factors. In this respect, particular role should be attributed to postmodernism which, by disproving the Enlightenment understanding of culture, undermined the role played by intellectuals.